OCCURRENCE OF ASYMPTOMATIC COVID-19 IN EMERGENCY SURGICAL PROCEDURES. MULTICENTER STUDY - Majeed, Farhan Ahmed; Ali, Ghazanfar; Aziz, Muhammad Asif; Shabbir, Hassan; Farhan, Nabeela; Sabir, Haroon (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find out the occurrence of Asymptomatic COVID-19 in emergency surgeries performed from 23 Mar to 23 Jun 2020 in three tertiary care hospitals and analyze the distribution of cases.Study Design: Cross sectional study.Place and Study Duration: Departments of Surgery, Combined Military Hospital Multan, Lahore and PNS Shifa Karachi from 23 Mar to 23 Jun 2020.Methodology: All cases requiring emergency surgical procedures were first assessed for clinical symptoms of COVID-19 and urgency for surgical intervention. Test for COVID-19 were advised in addition to baseline as per hospital policy. Patients requiring urgent intervention were operated using personal protective equipment (PPE) without waiting for COVID-19 test result while other emergency patients were operated after COVID-19 results within 24 hours.Results: Total 1941 patients were operated 678 (34.9%) in CMH Multan, 723 (37.2%) in CMH Lahore and 540 (27.8%) in PNS Shifa. Out of total 95(4.89%) patients were positive 57 (60%) male positive patients and female 38 (40%). Age distribution was max above 50 years with 33 (66%), only 13 were less than 20 years of age. All patients were clinically symptom free as per COVID-19 criteria of NIHConclusion: Of 4.89% patient can be missed COVID-19 cases if screening is not carried out in all patients undergoing surgery. Picking of these asymptomatic cases is rather more important as they can trigger spread in the healthcare workers and adversely affect the already overburdened health care delivery system in a close contact environment.